(untitled) (Revista Brasileira de Contabilidade e Gestão, 2024)
Innovation is a competitive advantage for companies in market disputes, especially regarding the engagement of consumers and other stakeholders. The capabilities of management and communication of innovation can decisively support the perception of a company’s market value, especially those listed on the stock exchange, whose share price fluctuates daily. This research aims to verify whether there is a correlation between communication about information and the turnover of companies listed on the Brazilian stock exchange (B3). The measurement consisted of elaborating and validating on a ordinal scale on the phenomenon of communication about innovation. For the construction of the scale, indicators that emerged from the literature on the subject were used, especially from ISO 56002 and the Global Innovation Index (GII). Oslo Manual guidelines were used for data collection, as well as for defining the sample and communication channels for prospecting. Thus, the procedures for construction and validation of the communication scale on innovation and the analysis of the results of the pre-test of correlation against the turnover of the companies in the sample are presented.